(untitled) (Global Journal of Medical Research, 2023)
Introduction Endpoint of resuscitation is essential to be determined objectively as we get more substantial evidence supporting the fact that both under resuscitation and over resuscitation is detrimental to overall outcomes Since carbon dioxide is more diffusible than oxygen it readily gets in to the blood in low perfusion states whereas oxygen doesn t Hence widening the PCO2 gap Since this PCO2 gap can be determined easily in the ICU we propose that PCO2 gap can be used as a reliable indicator of endpoint of resuscitation and predictor of mortality in patients with shock Aim To evaluate the association between PCO2 gap and outcome of resuscitation in patients with shock The Objectives of the project are to study the association between PCO2 difference and in-hospital mortality in patients admitted with shock and to study the correlation between PCO2 difference and lactate clearance